2012
DOI: 10.2169/internalmedicine.51.7845
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Onset Agranulocytosis and Hepatotoxicity after Taking Methimazole

Abstract: Agranulocytosis is a rare adverse effect of methimazole. The usual duration of treatment prior to the onset of agranulocytosis is approximately 1 to 4 months, and can be as long as 1 year. Agranulocytosis together with hepatotoxicity is an extremely rare idiosyncratic side effect of methimazole treatment. We present an unprecedented case of a Grave's disease patient who showed a strong reaction to methimazole with obvious agranulocytosis and hepatotoxicity which developed only six days after administration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…ANC, absolute neutrophil count; G-CSF, granulocyte-colony stimulating factor; -X±s, mean ± standard deviation patients developed sudden onset agranulocytosis and hepatotoxicity after taking methimazole within 6 days. This is the first case of agranulocytosis and hepatotoxicity induced by methimazole in less than 6 days [20]. The data from our study also revealed that the onset age, period of drug exposure, associated drugs (MMI or PTU) and neutrophil count on admission have no significant effect on the types of bone marrow.…”
Section: Clinical Characteristicssupporting
confidence: 52%
“…ANC, absolute neutrophil count; G-CSF, granulocyte-colony stimulating factor; -X±s, mean ± standard deviation patients developed sudden onset agranulocytosis and hepatotoxicity after taking methimazole within 6 days. This is the first case of agranulocytosis and hepatotoxicity induced by methimazole in less than 6 days [20]. The data from our study also revealed that the onset age, period of drug exposure, associated drugs (MMI or PTU) and neutrophil count on admission have no significant effect on the types of bone marrow.…”
Section: Clinical Characteristicssupporting
confidence: 52%
“…It has been shown in humans and rats that MMI is rapidly metabolised and that a major part is excreted via urine (Skellern & Steer 1981, Hengstmann & Hohn 1985, Cooper 2005, Kusmierek & Bald 2007. Nevertheless, MMI treatment sometimes induces severe side effects such as agranulocytosis and hepatotoxicity (Cooper 2005, Yang et al 2012, indicating that a significant amount of MMI and/or its metabolites is present in extra-thyroidal tissues. We measured the levels of reduced MMI and its oxidised metabolites in hens following 16 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 There is several human cases of PTU-induced hepatotoxicity. 15,[38][39] The mechanism(s) of PTU hepatotoxicity is obscure. In this study, we found that PTU caused mitochondrial dysfunction both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Several cases of PTU-induced hepatotoxicity have been reported. 4,[11][12][13][14][15][16] Pediatrics seems to be more vulnerable to PTU-induced hepatotoxicity. 17 There is no precise mechanism for PTU-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%